Synthesis of cadmium telluride nanoparticles for photovoltaic application - Chua, Kheng Hwee. (2010)
Cadmium Telluride (CdTe) nanorods with diameter of 3.7 nm and length of about 50 nm were successfully synthesized using the hot coordinating solvent method. Phase and composition characterization showed that the nanorods grew along the [001] direction and have the wurtzite structure. A systematic investigation of the reaction parameters, including the types of ligand for both Cd and Te complexes, the reaction temperature and the Cd:Te mole ratio, had been carried out. For the first time, it was concluded from our study that Te can be fully dissolved in the phosphine ligands at elevated temperature of about 190oC. From our results, it can be concluded that the optimum conditions to achieve high aspect ratio nanorods require the use of dodecylphosphonic acid (DDPA) and trioctylphosphine (TOP) as the complexing ligands for Cd and Te respectively and a high precursor concentration. It has also been observed that a high reaction temperature (≈290oC) favors high aspect ratio nanorod growth as compared with low reaction temperature (250oC).The effective monomer model can be used to explain the shape evolution of CdTe nanorods. The fabricated solar cells had Voc of 0.09978 V, Jsc of -0.03731 mA/cm2 and a Fill Factor of 0.28. The highest PCE recorded was 0.00103%. Presence of ligands on CdTe nanocrystal surfaces, unreacted precursor complexes and also the agglomeration of the nanorods could have limited the PCE by acting as recombination centers and affect the mobility of charge.